Geochemical Controls on Release and Speciation of Fe(II) and Mn(II) From Hyporheic Sediments of East River, Colorado - Dong, Wenming; Bhattacharyya, Amrita; Fox, Patricia M.; Bill, Markus; Dwivedi, Dipankar; Carrero, Sergio; Conrad, Mark; Nico, Peter S. (Frontiers in Water, 2020)
Hyporheic zones act as critical ecological links between terrestrial and aquatic systems where redox-sensitive metals of iron (Fe) and manganese (Mn) significantly impact nutrient cycling and water quality. However, the geochemical controls on the release and speciation of Fe(II) and Mn(II) in these biogeochemical hotspots are still poorly understood. Here we conducted batch incubation experiments and analyzed Fe K-edge extended X-ray absorption fine structure (EXAFS) spectroscopy data using sediment samples from a hyporheic zone of the East River floodplain in Colorado to understand the production, release and speciation of Fe(II) and Mn(II) in groundwater. Our results indicate that the production and release of Fe(II) and Mn(II) vary with sediment reducing conditions and subsurface positions, and the rates were determined either by a zero- or first-order rate equation. The sediments with higher Fe(II) production did not necessarily result in higher release of dissolved Fe(II), and  97% Fe(II) is accumulated in solid phase. We found that the majority of Fe(II) exists as siderite (FeCO3), Fe(II)-natural organic matter (NOM) complexes and ferrosmectite, and the equilibrium concentrations of dissolved Fe(II) are controlled primarily by siderite solubility, and enhanced greatly by formation of strong Fe(II)-NOM complexes as dominant aqueous Fe(II) species. By contract, dissolved Mn(II) increases slowly and linearly, and an equilibrium concentration was not reached during the incubation period, and the roles of rhodochrosite (MnCO3) and Mn(II)-NOM complexes are insignificant. Furthermore, we reviewed and calibrated the literature reported binding constants (log K) of Fe(II)-NOM complexes which successfully predicted our experimental data. This work reveals that siderite and dissolved NOM are the controlling phases in release and speciation of dissolved Fe(II), and the finding is expected to be applicable in many hyporheic zones and subsurface environments with similar geochemical conditions.